An Update on the Reversal of Non-Vitamin K Antagonist Oral Anticoagulants. (27th January 2020) - Mujer, Mark Terence P.; Rai, Manoj P.; Atti, Varunsiri; Dimaandal, Ian Limuel; Chan, Abigail S.; Shrotriya, Shiva; Gundabolu, Krishna; Dhakal, Prajwal
Abstract : Non-vitamin K antagonist oral anticoagulants (NOACs) include thrombin inhibitor dabigatran and coagulation factor Xa inhibitors rivaroxaban, apixaban, edoxaban, and betrixaban. NOACs have several benefits over warfarin, including faster time to the achieve effect, rapid onset of action, fewer documented food and drug interactions, lack of need for routine INR monitoring, and improved patient satisfaction. Local hemostatic measures, supportive care, and withholding the next NOAC dose are usually sufficient to achieve hemostasis among patients presenting with minor bleeding. The administration of reversal agents should be considered in patients on NOAC's with major bleeding manifestations (life-threatening bleeding, or major uncontrolled bleeding), or those who require rapid anticoagulant reversal for an emergent surgical procedure. The Food and Drug Administration (FDA) has approved two reversal agents for NOACs: idarucizumab for dabigatran and andexanet alfa for apixaban and rivaroxaban. The American College of Cardiology (ACC), American Heart Association (AHA), and Heart Rhythm Society (HRS) have released an updated guideline for the management of patients with atrial fibrillation that provides indications for the use of these reversal agents. In addition, the final results of the ANNEXA-4 study that evaluated the efficacy and safety of andexanet alfa were recently published. Several agents are in different phases of clinical trials, and among them, ciraparantag has shown promising results. However, their higher cost and limited availability remains a concern. Here, we provide a brief review of the available reversal agents for NOACs (nonspecific and specific), recent updates on reversal strategies, lab parameters (including point-of-care tests), NOAC resumption, and agents in development.